Gender Hierarchy in Qur’an Translation: A Critical Discourse Analysis of Al-Qur’an dan Terjemahnya Bahasa Palembang - Atfal, Khairul; Dendi Irwansa (Journal of Ushuluddin and Islamic Thought, 2024)
Discussions regarding the translation of the Qur’an into regional languages have undergone significant development in recent decades. This study aims to examine the translation of the Qur’an into the Palembang language, an initiative pioneered by the state, with a focus on how the translation team formulated gender hierarchy in the Qur’anic text. This study analyzes explicitly two key terms in Surah al-Nisā’ [4:34], namely min nafs wāḥidah and qawwāmūn . The method used is qualitative, relying on primary and secondary sources and employing Critical Discourse Analysis (CDA) framework to explore the relationship between the translated text and the surrounding social discourse. The results of the study indicate that the translation of the term min nafs wāḥidah in the Al-Qur’an dan Terjemahnya Bahasa Palembang reflects internal genealogical authority. Meanwhile, the term qawwāmūn is translated through two approaches: first, a genealogical approach that refers to previous translation traditions; second, a social approach influenced by the political dynamics of the campus as an institution under the auspices of the government, which has contributed to the strengthening of women’s roles in the public sphere—as seen in the election of female rectors for two consecutive terms. This study contributes to a deeper understanding of gender dynamics in local translations of the Qur’an by highlighting the interaction between religious texts, politics, and social contexts.